Durability properties and microstructure of ground granulated blast furnace slag cement concrete - Divsholi, Bahador Sabet (2015)
Ground granulated blast-furnace slag (GGBS) is a green construction material used to produce durable concrete. The secondary pozzolanic reactions can result in reduced pore connectivity; therefore, replacing partial amount of Portland cement (PC) with GGBS can significantly reduce the risk of sulfate attack, alkali–silica reactions and chloride penetration. However, it may also reduce the concrete resistance against carbonation. Due to the time consuming process of concrete carbonation, many researchers have used accelerated carbonation test to shorten the experimental time. However, there are always some uncertainties in the accelerated carbonation test results. Most importantly, the moisture content and moisture profile of the concrete before the carbonation test can significantly affect the test results. In this work, more than 200 samples with various water–cementitious material ratios and various replacement percentages of GGBS were cast. The compressive strength, electrical resistivity, chloride permeability and carbonation tests were conducted. The moisture loss and microstructure of concrete were studied. The partial replacement of PC with GGBS produced considerable improvement on various properties of concrete.